The Perbandingan Kualitas Hidup Peserta Prolanis Diabetes Melitus Tipe 2 yang Memperoleh Monoterapi dan Politerapi di Puskesmas Prambanan Sleman - Umsipyat , Annis Syafitri; Ananda, Raden Ajeng Dewinta Sukma; Nurinda , Eva; Wulandari, Ari Susiana (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Diabetes mellitus (DM) cases in the Yogyakarta Special Region in 2022 reached 42,050 patients (53.9%), with Sleman Regency having the highest prevalence. The therapy received by patients affects their clinical condition and quality of life. This study aims to determine the difference in the average quality of life of Prolanis DMT2 participants receiving monotherapy and polytherapy at Prambanan Public Health Center in Sleman. This research used an observational analytic study with a cross-sectional approach. The sample consists of 34 Prolanis participants at Prambanan Health Center, selected through total sampling. The instrument used is a quality-of-life questionnaire with a reverse Likert scale. The data analysis to measure quality of life is the Mann-Whitney statistics, using independent variables of monotherapy and polytherapy, and the dependent variable of quality of life scores. The majority of respondents are female (22 people, 66.7%), aged 56–65 years (16 people, 47.1%), and have a high school education level (15 people, 44.1%). Most are unemployed (21 people, 61.8%), have had diabetes for ≤ 5 years (26 people, 76.5%), and do not have complications (26 people, 76.5%). The average quality of life score for monotherapy is 28.88, and for polytherapy, it was 41.70. The quality of life for monotherapy is higher than for polytherapy, with a p-value of 0.001 (<0.05). This study aims to determine the difference in the average quality of life between Prolanis DMT2 participants receiving monotherapy and polytherapy at Prambanan Health Center in Sleman. Based on the research results, it was concluded that there is a difference in the average quality of life between Prolanis DMT2 participants at Puskesmas Prambanan Sleman who received monotherapy and those who received polytherapy, with a p-value of 0.001 (<0.05)